Magical Realism - Brownlee, Christopher Ian (My University, 2025)
My recent paintings explore the potential of magical and nonsensical imagery to evoke states of mind. I have studied mythology from many cultures, seeking to understand their non-rational logic. I apply that method of storytelling to narrative paintings, in the hope of capturing complex emotional states. My background is in realistic painting, but that no longer suits the work I’m doing. I seek an expressive mode of mark-making that better complements my non-linear approach to storytelling. I have applied this same myth-based method of organizing and presenting information to the writing of this thesis.
Thesis (Master's)--University of Washington, 2025
Keywords: drawing; mythology; narrative; oil painting; painting; Fine arts; Fine arts